Engineering the Morphology of Carbon Materials: 2D Porous Carbon Nanosheets for High‐Performance Supercapacitors. Issue 5 (29th February 2016) - Yuan, Kai; Hu, Ting; Xu, Yazhou; Graf, Robert; Brunklaus, Gunther; Forster, Michael; Chen, Yiwang; Scherf, Ullrich
Abstract: Compared with traditional porous carbon materials, two‐dimensional (2D) porous carbon materials with a high aspect ratio and a continuous hierarchical porous structure are promising candidates for the construction of supercapacitor electrode materials. Herein, well‐defined, graphene‐based conjugated microporous polymer sheets (G‐CMPs) were prepared in a graphene‐inspired synthetic strategy. Thereby, 4‐iodophenyl‐substituted graphene (RGO‐I) templates not only effectively hinder the aggregation between the adjacent graphene layers but also provide an efficient template for the growth of porous CMPs onto the graphene surface. Moreover, our G‐CMPs could be converted into 2D porous carbon nanosheets by pyrolysis. The synergism of high aspect ratio and high specific surface area, the presence of graphene‐based conduction paths and hierarchical pore systems ensure a high ion‐accessible surface area of the corresponding supercapacitor electrodes thus allowing accelerated electron and ion diffusion/transport and leading to high specific capacitance as well as good rate capability and cycling stability. Abstract : Separate sheets : Two‐dimensional porous carbon nanosheets are synthesized by pyrolysis of graphene‐templated conjugated microporous polymers for use as supercapacitor electrodes of promising performance and high rate capability and cycling stability.